PENGUKURAN KINERJA TENAGA KESEHATAN RUMAH SAKIT BERDASARKAN METODE MALCOLM BALDRIGE NATIONAL QUALITY AWARD - Labibah, Zulfa; Haksama, Setya (Journal of Digital Business and Innovation Management, 2023)
Performance is the most important aspect of hospital operations. Bed Occupancy Rate (BOR) shows the productivity of using inpatient beds and can also show the performance of the hospital staff. The BOR rate in the inpatient unit of RS X in 2020-2022 was below the ideal rate of 60-85%. This study aims to measure the performance of the inpatient unit of RS X based on the seven Malcolm Baldrige criteria. This type of research is descriptive research with a cross-sectional approach. The population in this research is all nurses of the inpatient unit of X Hospital which amounted to 201 people. The sample was taken using simple random sampling method and calculated the proportion of each room with a sample size of 138 people. Data were collected using a questionnaire consisting of 49 statements. The results of the study obtained a percentage of achievement based on the Malcolm Baldrige score on leadership criteria of 85.25%, strategic planning criteria of 84.0%, customer focus criteria of 86.94%, PAMP criteria of 82.89%, human resource focus criteria of 84.94%, operational focus criteria of 85.88%, and results criteria of 83.58%. Overall performance achievements based on the seven Malcolm Baldrige criteria are in the excellent level 2 category, except for the measurement, analysis, and knowledge management criteria which are in the excellent level 1 category. So, efforts still need to be made to improve performance in the inpatient unit, especially in the measurement, analysis, and knowledge management categories.